3D printing of active mechanical metamaterials: A critical review - Khalid, Muhammad Yasir; Arif, Zia Ullah; Tariq, Ali; Hossain, Mokarram; Umer, Rehan; Bodaghi, Mahdi (Materials & design, 2024)
[Display omitted] •Studying 4D printed-based mechanical metamaterials systematically.•Reviewing multifunctional energy-absorbing and shape-morphing features.•Outlining applications of 4D printed-based mechanical metamaterials.•Discussing multifaceted challenges with proposed solutions. The emergence of mechanical metamaterials from 4D printing has paved the way for developing advanced hierarchical structures with superior multifunctionalities. In particular, 4D-printed mechanical metamaterials exhibit extraordinary mechanical performance by integrating multiphysics stimuli with advanced structures when actuated by external factors, thereby altering their shapes, properties, and functionalities. This critical review offers readers a comprehensive overview of the rapidly growing 4D printing technology for developing novel mechanical metamaterials. It provides essential information about the multifunctionalities of 4D-printed mechanical metamaterials, including energy absorption and shape-morphing behavior in response to physical, chemical, or mechanical stimuli. These capabilities are key to developing smart and intelligent structures for multifunctional applications such as biomedical, photonics, acoustics, energy storage, and thermal insulation. The primary focus of this review is to describe the structural and functional applications of mechanical metamaterials developed through 4D printing. This technology leverages the shape-shifting functions of smart materials in applications such as micro-grippers, soft robots, biomedical devices, and self-deployable structures. Additionally, the review addresses current progress and challenges in the field of 4D-printed mechanical metamaterials. In conclusion, recent developments in 4D-printed mechanical metamaterials could establish a new paradigm for applications in engineering and science.